Monocarboxylate transporter 1 is up-regulated in basal-like breast carcinoma - Pinheiro, Céline (2010)
Monocarboxylate transporters (MCTs) have been considered promising targets for cancer therapy, since they facilitate lactate efflux in glycolytic tumours. However, their role in solid tumours is still poorly understood. Thus, the present work aimed to contribute to understanding the involvement of MCT1 and MCT4 in breast cancer progression as well as MCT regulation by CD147.